(untitled) (Journal of Forensic Medicine & Toxicology, 2020)
Suicides make a substantial contribution to the numbers of premature deaths, and to inform policies that might prevent suicide there is a need for improved knowledge about risk factors. A retrospective analysis of the post mortem records of the suicide cases which were brought to the mortuary of a teaching institute in north east India was carried out. Data were analyzed with regard to age and sex, occupation, social status, seasonal variation, immediate precipitating event, mode of suicide and place of suicide to determine the trend of suicide and factors influencing suicidal behavior. The findings are correlated with the results of other studies in various parts of the world. Unemployment played a major role. It is also observed that unfavorable outcome in examinations and failure of crops during the harvest season could be important factors influencing suicidal behavior.